TUMBUHAN OBAT TRADISIONAL SEBAGAI INDIGENOUS KNOWLEDGE MASYARAKAT SUNDA: KAJIAN ETNOPEDAGOGIK - Dewi, Cipta Wisuda; Koswara, Dedi; Darajat, Danan (Magistra Andalusia: Jurnal Ilmu Sastra, 2024)
This study discusses the use of traditional medicinal plants from an ethnopedagogical perspective, focusing on a case study in the Sundanese community. The research aims to understand the traditional healing practices involving the use of medicinal plants among the Sundanese people and how the ethnopedagogical approach can be used to uncover local knowledge and strengthen these cultural practices. The research methodology employed is a qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation study. The research sample was purposively selected, involving community leaders or traditional healing experts with extensive knowledge of medicinal plants and traditional healing practices in the Sundanese community. The results show that the use of traditional medicinal plants remains an integral part of the Sundanese healthcare system. These plants are used to treat various diseases and health disorders, serving as symbols of local wisdom and cultural identity. The ethnopedagogical approach facilitates the sustainable transfer of knowledge from generation to generation and raises awareness of the importance of preserving cultural heritage in the context of traditional medicine.